Development and Validation of a Patient-Reported Outcome Questionnaire for Children Undergoing Removable Orthodontic Treatment - Panaite Tinela; Carmen Diana Nicoleta Savin; Ana Sîrghie; Teona Ana-Maria Tudorici; Irina Bamboi; Anca Rapis; Ana Nemțoi; Ciprian-Iulian Axinte; Carina Ana-Maria Balcos (Dentistry Journal, 2026)
Background/Objectives: Patient-reported outcome measures (PROMs) complement clinical indicators in orthodontics, yet validated instruments for children undergoing removable orthodontic treatment remain limited. This study aimed to develop and validate a questionnaire assessing compliance and physical discomfort, psychosocial impact, and perceived support. Methods: A cross-sectional validation study included 250 children and adolescents (